(untitled) - Hossner, K. L. (Wallingford, Oxfordshire, UK, 2005)
This book describes the cellular and molecular mechanisms that are involved with the regulation of cell and tissue growth, including development and body composition. The emphasis is on circulating hormones, local growth factors and gene transcription factors which regulate growth and differentiation of skeletal muscle, bone and adipose tissue. This book starts by introducing the reader to basic aspects of whole animal growth and presents an outline of the important concepts in molecular and cell biology that are required for an understanding of the processes of animal growth control. It then goes on to explain the endocrine system along with hormonal regulation and the relationship of specific hormones to domestic animal growth.
Những tiến bộ khoa học mới về sinh lý sản xuất động vật
Keywords: Livestock,Hormones,Growth regulators,Chăn nuôi,Kích thích tố,Điều chỉnh tăng trưởng; Growth,Regulation,Tăng trưởng,Sự điều chỉnh